PENERAPAN STRATEGI PEMBELAJARAN MOTIVASIONAL DENGAN PERMAINAN KARTU BERTEMA PROTISTA PADA SISWA KELAS X SMA - Rahmaniati, Ernita (Universitas Tanjungpura, 2016)
This research is motivated tendency in the field of biology shows that learning outcomes in protists material has not achieved the expected results. This is because teachers are more active than the students, so that the learning-oriented teacher (teacher-oriented) whereas passive during the learning of their students as well as the presentation of learning materials in the classroom is still conventional. This type of research is Classroom Action Research (PTK). Data taken using test instruments, observation sheet and test evaluation of learning outcomes is a means of collecting qualitative data processed. The results showed that by application of learning strategy discovery learning using protists themed card game can improve motivation and results of students of class X MIA1 SMA 4 PontianakKeywords : Motivation, learning outcomes, card game, Discovery Learning